Design of Ultrathin Pt‐Based Multimetallic Nanostructures for Efficient Oxygen Reduction Electrocatalysis. Issue 48 (8th November 2017) - Lai, Jianping; Guo, Shaojun
Abstract: Nanocatalysts with high platinum (Pt) utilization efficiency are attracting extensive attention for oxygen reduction reactions (ORR) conducted at the cathode of fuel cells. Ultrathin Pt‐based multimetallic nanostructures show obvious advantages in accelerating the sluggish cathodic ORR due to their ultrahigh Pt utilization efficiency. A focus on recent important developments is provided in using wet chemistry techniques for making/tuning the multimetallic nanostructures with high Pt utilization efficiency for boosting ORR activity and durability. First, new synthetic methods for multimetallic core/shell nanoparticles with ultrathin shell sizes for achieving highly efficient ORR catalysts are reviewed. To obtain better ORR activity and stability, multimetallic nanowires or nanosheets with well‐defined structure and surface are further highlighted. Furthermore, ultrathin Pt‐based multimetallic nanoframes that feature 3D molecularly accessible surfaces for achieving more efficient ORR catalysis are discussed. Finally, the remaining challenges and outlooks for the future will be provided for this promising research field. Abstract : Recent progress in designing ultrathin Pt‐based multimetallic nanostructures for efficient oxygen reduction electrocatalysis is reviewed. Examples of various colloid methods for making/tuning ultrathin Pt‐based multimetallic nanostructures are provided, and studies on the underlying structure–performance relationship are presented.